РЕСПУБЛИКАМЫЗДЫҢ АЎЫЛ ХОЖАЛЫҒЫНДАҒЫ АЛЫП БАРЫЛЫП АТЫРҒАН ЖЕТИСКЕНЛИКЛЕР - Хожалепесов, П.З.; Зинатдинов, Б.П.; Жорабаева, Ж.К. (FAN va JAMIYAT, 2019)
The article is devoted to the description of the reforms in the agricultural sector of the republic. The author of the article also studies the ways of providing the agriculture of the republic with mineral fertilizers and ways of its financing in conditions of market economy.